The Effect of Posting Timeliness and Brand Awareness Quality Content and Sales Figures on Premium Sustainable Fashion Products (MSDM Literature Review) - Daesy Christina Tjahjadi (Dinasti Publisher, 2023)
Literature Review Articles on the Effect of Timely Posting and Quality Content on Brand Awareness and Sales Figures in Premium Fashion Accessory Products is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of Marketing Management science. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) Timeliness of posting has an effect on brand awareness; 2) Quality content has an effect on brand awareness; 3) Timeliness of posting affects sales figures; 4) Quality content affects sales figures; and 5) Brand awareness affects sales figures. Apart from these 2 exogenous variables that affect the endogenous variables of brand awareness and sales figures there are still many other factors including the variable type of content (media used), engagement and influencers used by the brand.